Differential sprouting ability during micropropagation of Nidularium minutum Mez (Bromeliaceae) - Maria Gessi Teixeira; Catarina Carvalho Nievola (Acta Scientiarum. Biological Sciences, 2023)
Nidularium minutum is an ornamental bromeliad from the Brazilian Rainforest. The micropropagation of this species is essential for obtaining plants available for conservation programs or commercial use. Our study aimed to establish an efficient plant production method by in vitro sprouting. This bromeliad takes a long time to sprout in vitro, and 10% of the plants produce shoots in a culture medium without plant growth regulators (PGRs). When subcultured in a PGR-free medium, these individualized shoots can sprout like the mother plant. The Murashige and Skoog basal medium (MS) containing 1.0 mg L-1 of 6-benzylaminopurine (BAP) promoted the induction of adventitious shoots in greater than 90% of the plants after 240 days of culture with an average of more than eight shoots per plant. Approximately 100% of the in vitro-produced shoots survived after acclimatization, reaching the flowering stage. Therefore, our results showed that in vitro regeneration of N. minutum depends on the cultivation period and that plants with a higher sprouting capacity can be selected and used as micropropagation matrices, contributing to the production of this endangered bromeliad.